New directions for system support in pervasive computing - Rodrigues, Helena (2012)
In this paper, we discuss alternative paths towards system support for Pervasive Computing that are based on a balanced combination between global services and situated devices that we hypothesise will be the key to widespread deployment of Pervasive Computing: global services provide functionality that can be relevant anywhere, thus obviating the need to create dedicated services on a case-by-case basis; situated devices, such as displays, networks, and mobile phones, provide context and enable meaningful links between global services and the physical environment. It also considers the implications of a Crowdsourced system software development model. In these systems, specialised teams construct the kernel- level services, such as managing information about physical devices, presences, interactions or active applications, on which subsequent development is based. Complementary, developers and prosumers co-create the value in Pervasive Computing by explicitly defining the system boundary and making the association between applications and physical devices.